Changes in exposure to ambient fine particulate matter after relocating and long term survival in Canada: quasi-experimental study. (8th October 2021) - Chen, Hong; Kaufman, Jay S; Olaniyan, Toyib; Pinault, Lauren; Tjepkema, Michael; Chen, Li; van Donkelaar, Aaron; Martin, Randall V; Hystad, Perry; Chen, Chen; Kirby-McGregor, Megan; Bai, Li; et al.
Abstract: Objective: To investigate the association between changes in long term residential exposure to ambient fine particulate matter (PM2.5 ) and premature mortality in Canada. Design: Population based quasi-experimental study. Setting: Canada. Participants: 663 100 respondents to the 1996, 2001, and 2006 Canadian censuses aged 25-89 years who had consistently lived in areas with either high or low PM2.5 levels over five years preceding census day and moved during the ensuing five years. Interventions: Changes in long term exposure to PM2.5 arising from residential mobility. Main outcome measures: The primary outcome was deaths from natural causes. Secondary outcomes were deaths from any cardiometabolic cause, any respiratory cause, and any cancer cause. All outcomes were obtained from the national vital statistics database. Results: Using a propensity score matching technique with numerous personal, socioeconomic, health, and environment related covariates, each participant who moved to a different PM2.5 area was matched with up to three participants who moved within the same PM2.5 area. In the matched groups that moved from high to intermediate or low PM2.5 areas, residential mobility was associated with a decline in annual PM2.5 exposure from 10.6 μg/m 3 to 7.4 and 5.0 μg/m 3, respectively. Conversely, in the matched groups that moved from low to intermediate or high PM2.5 areas, annual PM2.5 increased from 4.6 μg/m 3 to 6.7 and 9.2 μg/m 3 . Five years after moving, individuals who experienced a reduction in exposure to PM2.5 from high to intermediate levels showed a 6.8% (95% confidence interval 1.7% to 11.7%) reduction in mortality (2510 deaths in 56 025 v 4925 deaths in 101 960). A greater decline in mortality occurred among those exposed to a larger reduction in PM2.5 . Increased mortality was found with exposure to PM2.5 from low to high levels, and to a lesser degree from low to intermediate levels. Furthermore, the decreases in PM2.5 exposure were most strongly associated with reductions in cardiometabolic deaths, whereas the increases in PM2.5 exposure were mostly related to respiratory deaths. No strong evidence was found for the changes in PM2.5 exposure with cancer related deaths. Conclusions: In Canada, decreases in PM2.5 were associated with lower mortality, whereas increases in PM2.5 were associated with higher mortality. These results were observed at PM2.5 levels considerably lower than many other countries, providing support for continuously improving air quality.